Pengaruh Asam Alfa Lipoat Terhadap Kadar Trigliserida pada Tikus Diabetes Melitus Tipe 2 - Angel Chen; Ismawati Ismawati; Enikarmila Asni (Fakultas Kedokteran Universitas Riau, 2018)
Accumulation of triglycerides associated with insulin resistance in type 2 diabetes mellitus (T2DM). Alpha lipoic acid (ALA) has hypotriglyceridemic effects by lowering triglyceride levels in blood and liver. This study aims to analyze effect of ALA on triglyceride levels in type 2 diabetic rats. Fifteen Wistar male rats (±8-12 weeks, 200-250 gram) divided into 3 groups (control, T2DM and T2DM–ALA given for 3 weeks). Diabetes was induced by giving streptozotocin (50 mg/kg.bw) and nicotinamide (110 mg/kg.bw) after 15 minutes intraperitoneally. Diagnosis of T2DM was determined if the rats have perifer blood glucose >250 mg/dL after 3 days. The results showed that triglyceride levels in ALA group (p=0,003) lower than T2DM group, T2DM group (p=0,031) had higher triglyceride level than control and no difference of triglyceride level between T2DM-ALA given group with control (p=0,696). This study concluded that ALA can affect triglyceride levels in T2DM thus prevents occurrence of hypertriglyceridemia.